2010
DOI: 10.1093/jac/dkq370
|View full text |Cite
|
Sign up to set email alerts
|

Tigecycline activity: low resistance rates but problematic disc breakpoints revealed by a multicentre sentinel survey in the UK

Abstract: Tigecycline resistance was rare in isolates causing clinically significant infections in the UK and was overestimated ∼2-fold by the BSAC disc method. Adjustment of the breakpoints might overcome this problem but at the risk of increasing the false susceptibility rate. The best advice is to perform dilution tests, e.g. by gradient strip test on isolates with borderline results, especially in severe infection and when tigecycline use is intended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…Clinical labs using disc diffusion on a daily basis could properly categorize true tigecycline susceptible and resistant strains by using a zone breakpoint of susceptible ≥ 21 mm and resistant ≤ 16 mm (VME and MaE 0%) (Mueller-Hinton agar from Difco, BD, New Jersey, US). Strains with halos between 17-20 mm could fall in any of the three MIC categories, although most of the isolates had a trend toward susceptibility by the reference (MIC) method, as has been also observed in other study using the BSAC method [12]. We observed in this series that 40% of strains with intermediate halos showed susceptibility by MIC, and only 7% resulted true resistant.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Clinical labs using disc diffusion on a daily basis could properly categorize true tigecycline susceptible and resistant strains by using a zone breakpoint of susceptible ≥ 21 mm and resistant ≤ 16 mm (VME and MaE 0%) (Mueller-Hinton agar from Difco, BD, New Jersey, US). Strains with halos between 17-20 mm could fall in any of the three MIC categories, although most of the isolates had a trend toward susceptibility by the reference (MIC) method, as has been also observed in other study using the BSAC method [12]. We observed in this series that 40% of strains with intermediate halos showed susceptibility by MIC, and only 7% resulted true resistant.…”
Section: Resultssupporting
confidence: 84%
“…The strains were submitted to the National Reference Laboratory because they either had an XDR phenotype (50% of the isolates) or required a tigecycline/fosfomycin MIC confirmation. The resistant mechanisms were characterized by PCR and DNA sequencing and included (n): KPC (70), CTX-M-2 plus porin loss (21), OXA-163 (3), IMP-8 (3), VIM-2 (2), VIM-1 (1), NDM-1 (1), OXA-48-like (1), ESBLs (CTXM-2, PER-2, SHV-2, SHV-5, SHV-18) (76), narrow-spectrum beta-lactamases (6), and wild type isolates (including ATCC quality control strains) (12). The isolates were from clinical sources and they were single isolates from each patient.…”
Section: Methodsmentioning
confidence: 99%
“…The interchangeability of tigecycline susceptibility results of CR Enterobacteriaceae and A. baumannii is not well defined (13). Previous studies have reported discrepant Etest and BMD results with tigecycline, mainly for A. baumannii (3,7,10,12,14,19,22). Scarce data are available on the accuracy of VItek2 with MDR pathogens (15).…”
Section: Susceptibility Testing Methodsmentioning
confidence: 99%
“…It has been previously noted that discrepancies may exist when different methods are used (3,7,14,19,22). It was also reported that disk diffusion and Etest have a poor correlation with BMD, especially for A. baumannii (3,10,12,22). Furthermore, the accuracy of the Vitek2 automated system (bioMérieux, Marcy l' Etoile, France) has not been adequately evaluated for tigecycline (15).…”
mentioning
confidence: 99%
“…Tigecycline is a member of the glycylcycline group of antibiotics, and was registered in the EU in April 2006 [18]. This bacteriostatic antibiotic acts as a protein synthesis inhibitor by binding to the 30S ribosomal subunit [19].…”
Section: Introductionmentioning
confidence: 99%